HARMONY AND DIVERSITY IN YOGYAKARTA URBAN AREAS: MEASURING THE RELIGIOUS MODERATION INDEX IN BALEHARJO AND SINDUADI SUBDISTRICTS - Muh Ulil Absor; Asep Jahidin; Muqowim Muqowim; Hijrian Angga Prihantoro; Achmad Zuhri; Proborini Hastuti (Al-Qalam, 2022)
The development of extreme religious perspectives, attitudes of subjective truth claims that impose their religious interpretations are the main basis for the need for a moderate religious perspective. This article aims to analyse the situation of harmony, the experience of discrimination based on religion and to examine the religious moderation attitudes in the community. This research was conducted in a multicultural urban area in the Province of DI Yogyakarta, Baleharjo and Sinduadi Villages. This study found that respondents who experienced discrimination due to their religion were very low. However, 10.2% of respondents reported that there had been friction in their community. This study also found that level of people's attitudes regarding religious moderation measured by national commitment, tolerance, non-violence and accommodativeness to local culture can be categorized as high or good. However, there are several aspects of religious moderation that need to be strengthened such as attitudes about the importance of solving problems through legal approach if a person has problems with followers of other religions, acceptance of the establishment of houses of worship of other religions, leaders from other religions and the desire to conduct demonstrations and expel groups that are considered deviant. This study also found that the higher the education of the respondents, the higher the average score of religious moderation. Respondents who are active in religious organizations have also a higher attitude of religious moderation. Education, both through formal education and religious activities, can be an effective strategy to strengthen religious moderation attitudes in society.